1983
DOI: 10.1161/01.hyp.5.2_pt_2.i119
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new strain of spontaneously hypertensive rats homozygous for hypothalamic diabetes insipidus.

Abstract: SUMMARY The aim of the present study was to investigate whether the presence of arginine vasopressin (AVP) is necessary for the establishment of high blood pressure in spontaneously hypertensive rats (SHR). For this purpose we crossbred SHR of the stroke-prone substrain (SHRSP) with rats homozygous for hypothalamic diabetes insipidus of the Brattleboro strain (DI) which are unable to synthetize AVP. The successful introduction of the DI gene into the SHRSP strain (SHRDI) was demonstrated by the following obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…This procedure led to a stepwise accumulation of SHR genes and a reappearance of DI animals from the DI/+XDI/-intercrosses. 7 Results with these SHRSP-DI animals showed that blood pressure developed essentially the same way as in SHRSPs with respect to absolute levels and time course (Figure 3). The mortality of the resulting SHRSP-DI offspring was high.…”
Section: Introduction Of a Mutated Gene: The Spontaneously Hypertensimentioning
confidence: 68%
See 2 more Smart Citations
“…This procedure led to a stepwise accumulation of SHR genes and a reappearance of DI animals from the DI/+XDI/-intercrosses. 7 Results with these SHRSP-DI animals showed that blood pressure developed essentially the same way as in SHRSPs with respect to absolute levels and time course (Figure 3). The mortality of the resulting SHRSP-DI offspring was high.…”
Section: Introduction Of a Mutated Gene: The Spontaneously Hypertensimentioning
confidence: 68%
“…This marks the important transition from classic breeding, the experiments of nature, to high-tech genetics, which offers previously impossible and unparalleled opportunities. 89 This review of our efforts to develop new animal models of experimental hypertension research is based on previously published reports on the gene analysis in SHRs, 3 -6 the introduction of mutated genes resulting in SHRs with hereditary hypothalamic DI (SHR-DI), 7 and the generation of hypertensive transgenic rats with an additional renin gene TGR(mRen-2 d ) 27.»-tension occurs frequently (95%). Animal models for primary hypertension therefore are needed, particularly ones with hereditary transmitted hypertension, to study the genetics of this disease.…”
Section: Invited Lecturementioning
confidence: 99%
See 1 more Smart Citation
“…The development of a strain of SHR with diabetes insipidus 42 does not eliminate these possibilities, because the abnormalities in the VP system in the strokeprone strain of SHR used in the cross-breeding experiments are different from the abnormalities in the non-stroke-prone strain used in the present study. In the stroke-prone strain of SHR, VP does not contribute to the development of hypertension, but it may participate in maintaining pressure during the chronic phase.…”
mentioning
confidence: 79%
“…Therefore, an imbalance between the intensity of vasoconstrictive V1a and nitric oxide-generating V2 effects could be ex-pected to alter BP regulation. Ganten et al (9) developed a strain of spontaneously hypertensive rats that also are homozygous for central diabetes insipidus (Brattleboro strain). The rats developed hypertension nonetheless, even though their vasopressin concentrations are zero, thereby showing that vasopressin actions are not a prerequisite in all forms of hypertension.…”
mentioning
confidence: 99%